Organizational Learning and Self-Efficacy as the mediators in the Organizational Culture impact on the Employee’s Performance - Hasan, Halid (JPAS (Journal of Public Administration Studies), 2020)
This study investigated the mediating effects of organizational learning and self-efficacy on the relationship between organizational culture and employee performance. The sample consisted of 172 employees of government owned banking institutions in Malang district, Indonesia. Results, using path analysis reveal that all the variables examined positively and significantly affect employee performance. This study found that organizational learning and self-efficacy mediated the relationship between organizational culture and employee performance.